Translocator protein (18kDa TSPO) binding, a marker of microglia, is reduced in major depression during cognitive-behavioral therapy - Li, Hua; Sagar, Aadi P.; Kéri, Szabolcs (Progress in neuro-psychopharmacology & biological psychiatry, 2018)
Prior studies indicated that neuroinflammation might play a role in the pathophysiology of major depressive disorder (MDD). The purpose of this study was to examine changes in a microglial marker in the brain of patients with MDD during cognitive-behavioral therapy (CBT) and supportive psychotherapy (SPT). Participants were newly diagnosed patients with MDD receiving CBT (n=20) or SPT (n=20) who were compared with 20 healthy control subjects. We used [18F]-FEPPA positron emission tomography (PET) to examine translocator protein total distribution volume (TSPO VT), a marker of microglial density and inflammation. Patients were scanned before and after CBT and SPT. Before therapy, TSPO VT was significantly elevated in neocortical grey matter, frontal cortex, temporal cortex, and hippocampus in MDD relative to the control subjects. In the CBT group, but not in the SPT group, TSPO VT was significantly reduced during the treatment period. Reductions in TSPO VT were correlated with the amelioration of depressive symptoms. This correlation was consistent in the hippocampus in both CBT and SPT groups. In conclusion, CBT, when it reduced symptoms, also decreased TSPO VT. Efficient psychosocial interventions were accompanied by the normalization of a glial marker in the brain of patients with MDD, which may indicate reduced pro-inflammatory activity. •TSPO VT is elevated in major depression indicating neuroinflammation.•TSPO VT is decreased during cognitive-behavior therapy.•Decreased TSPO VT correlates with the reduction of depression.